Institutional Management Planning In Improving The Quality Of Paud In Kindergarten Naurahhuda Karawang - Anita Kresnawaty; Iim Wasliman; Hanafiah; Faiz Karim Fatkhullah (CV. AFDIFAL MAJU BERKAH, 2022)
Abstract Early childhood education (PAUD) is a strong foundation in preparing the nation's next generation to continue education at the next level. Early childhood is the basic human foundation in placing important stimulations that can jump-start children's growth and development functions including cognitive development, language, physical motor, social emotional, religious and moral development as well as art development. This study aims to determine the planning in the management of Early Childhood Education. The research method used is descriptive qualitative with literacy studies and involves research subjects, namely at Naurahhuda Kindergarten, Karawang. The conclusion in this study is that the management of Early Childhood Education requires clear planning for the management of PAUD and managers must understand management standards for the management of directed and better Early Childhood Education. Understand the principles of management and the main tasks of the functions of each stakeholder involved in it